Seroprevalence of Measles-, Mumps-, and Rubella-specific antibodies in the German adult population - cross-sectional analysis of the German Health Interview and Examination Survey for Adults (DEGS1) - Nicole Friedrich; Christina Poethko-Müller; Ronny Kuhnert; Dorothea Matysiak-Klose; Judith Koch; Ole Wichmann; Sabine Santibanez; Annette Mankertz (Elsevier, 2021)
Background: The WHO European Region targets the elimination of measles, rubella, and the congenital rubella syndrome and welcomes mumps elimination via the joint MMR vaccine. In a push towards this elimination goal, Germany introduced a recommendation on MMR vaccination for adults in 2010 to prevent increasing numbers of measles cases among adults and to strengthen herd immunity. Methods: The prevalence of anti-measles, -mumps, and -rubella IgG antibodies was analysed in 7,115 participants between the ages of 18 and 79 years in the German Health Interview and Examination Survey. Risk factors of seronegativity of adults born 1970 or later were determined. Findings: The seroprevalence of anti-measles IgG antibodies was more than 97% in adults born before 1965 and less than 90% in adults born afterwards. Prevalence and GMTs declined with later years of birth. Seronegativity was associated with two-sided migration background and region of residence in East Germany. For anti-mumps IgG antibodies, the seroprevalence was less than 90% in almost all age groups. Prevalence and GMTs declined with later years of birth. Seronegativity was not associated with any socio-demographic factor. Anti-rubella IgG seropositivity was found in more than 90% of adults born before 1985. GMTs declined in younger age groups. Seronegativity was associated with birth between 1980 and 1993 and male gender. High socio-economic status lowered the odds of being seronegative. Interpretation: These data reinforce the implementation of the vaccination recommendation for adults and provide the basis for further evaluation of this measure. Funding: The Federal Ministry of Health, Germany.